Application of workfunction engineering in vertical superjunction devices. (September 2017) - Nautiyal, Payal; Naugarhiya, Alok; Verma, Shrish
Abstract: A novel device superjunction vertical single diffused metal oxide semiconductor (SJ VSDMOS) employing work function engineering has been proposed in this paper. Electron and hole plasma formation take place due to the work function difference at the metal-semiconductor contact. Electron plasma is formed below source contact, above drain terminal and hole plasma below body contact. Further, we have investigated the electrical characteristics of both conventional and proposed device. We have demonstrated that the proposed device performance is better in comparison with conventional device as 8 % rise in the drain current density of proposed device is observed without affecting the breakdown voltage. Increment in current will lead to reduction in number of cells needed for a specific application. Further, the proposed device eliminates two process steps during fabrication by completely eradicating the use of aluminum as metal. Highlights: Implementation of work function engineering in Superjunction vertical device. Hf and Pt are used as source/drain metal contact instead of Al. Hf is used to create "n+" region at source, drain and Pt to create hole plasma. The proposed device results in increase in 8% drain current density. Leading to reduction of Ron A needed for a particular application.